The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles